Exploring shared therapeutic targets for Alzheimer’s disease and glioblastoma using network pharmacology and protein-protein interaction approach - Pradeep, Sushma; Sai Chakith, M. R.; Sindhushree, S. R.; Reddy, Pruthvish; Sushmitha, Esther; Purohit, Madhusudan N.; Suresh, Divya; Swamy Shivananju, Nanjunda; Silina, Ekaterina; Manturova, Natalia; Stupin, Victor; Kollur, Shiva Prasad; et al. (Frontiers in Chemistry, 2025)
BackgroundAlzheimer’s disease (AD) and glioblastoma (GBM) are complex neurological disorders with distinct pathologies but overlapping molecular mechanisms, including neuroinflammation, oxidative stress, and dysregulated signaling pathways. Despite significant advancements in research, effective therapies targeting both conditions remain elusive. Identifying shared molecular targets and potential therapeutic agents could offer novel treatment strategies for these disorders.MethodologyThe study employs an integrative network pharmacology approach to explore the therapeutic potential of bioactive compounds from Eclipta alba, a medicinal herb known for its neuroprotective and anti-inflammatory properties. A systematic methodology was adopted, starting with network pharmacology analysis using STRING and DisGeNET databases, which identified 617 common genes associated with AD and GBM. Among these, key hub genes—TP53, STAT3, AKT1, and IL6—were prioritized using Cytoscape for network visualization and analysis.ResultsMolecular docking studies were conducted using PyRx software to assess the binding interactions of 26 phytochemicals from Eclipta alba against the identified target genes. Luteolin exhibited the highest binding affinity to IL6 (−7.8 kcal/mol), forming stable hydrogen bonds and hydrophobic interactions. To further validate this interaction, molecular dynamics simulations (MDS) were performed using GROMACS, confirming the stability of the Luteolin-IL6 complex. Additionally, MM-PBSA binding energy calculations using AmberTools (−145.44 kJ/mol) provided further evidence of a strong and stable interaction. Pharmacokinetic and toxicity evaluations, conducted using SwissADME and pkCSM, highlighted luteolin’s favorable drug-like properties, including good bioavailability and low toxicity. These findings suggest that luteolin may serve as a promising multi-target therapeutic agent for AD and GBM by modulating key pathological pathways.ConclusionThe present study provides a strong computational foundation for further in vitro and in vivo validation. The results highlight the potential of luteolin in developing dual-target treatment strategies for neurodegenerative and oncological disorders, offering new avenues for therapeutic advancements.